THE FACTORS THAT INFLUENCE MOTHER'S BEHAVIOR IN GIVING FOOD COMPLEMENT OF BREAST MILK FOR BABY IN AGE 6 - 36 MONTH - Kristianto, Yonatan; Sulistyarini, Tri (Jurnal Penelitian STIKES Kediri, 2013)
Food complement of breast milk is food that contain nutrient, giving to child in age 6–36 months to complete nutrient requirement. Giving that food is precisely influenced by mother’s behavior who have baby. The objective of the research to prove the factors that influence mother’s behavior in giving food complement breast milk to child in age 6–36 months.The design of the research was correlation. The population was all mother who have children in age 6–36 months at Posyandu Mawar I Karangrejo village. The samples were 32 respondents using random sampling. The independent variable was the factors that influence of mother’s behavior. The dependent variable was giving food complement of breast milk. The data was collected using questionnaire and interview, and then analyzed using multiple logistic regression with significance level 0,025. The result of statistical test showed mother’s knowledge p=0,020, it mean  influence mother’s behavior in giving food complement of breast milk. The conclusion of this research that the occupation factor and social economy had no influence mother’s behavior in giving food complement of breast milk, but mother’s knowledge had influence mother’s behavior in giving food complement of breast milk at Posyandu Mawar I Karangrejo village.